KALIMAT EFEKTIF DALAM KOMUNIKASI FORMAL - Sudarwati Sudarwati; Y.B Agung Prasaja (Universitas 17 Agustus 1945 Surabaya, 2015)
ABSTRACT. In communication, language becomes a dominant element. In a formal situation, such as in an academic activity, it is the formal language that is used. One of the features of a formal language is that the whole sentences are in the form of effective sentences. Effective sentences require: economical sentence; having a logical meaning of the sentence; the existence of clear subject and predicate; well parallel row of words; firmly sentence meaning; solid-grammatical word group; no interferences of foreignÂ structure and vocabulary; no redundancy; no discriminating words; applying Indonesian Spelling System (EYD) accurately and consistently.Â Key words: ragam bahasa formal, kalimat efektif, komunikasi, Ejaan Yang Disempurnakan (EYD)